Validation of farmer to farmer extension model for dissemination of quality seeds of pulse crops: experiences from Bundelkhand Region of Uttar Pradesh - Uma Sah, Narendra Kumar, Hem Saxena, S.K. Dubey, M.A. Iquebal, Shripad Bhat; S.K. Singh (Indian Journal of Extension Education, 2018)
The study was conducted during 2010-14 at Indian Institute of Pulses Research (IIPR), Kanpur among 143 farmers from Jalaun district of Bundelkhand region of India. The key farmers were provided quality seeds of improved pulse varieties and they were asked to diffuse the seeds in a pre designed structured manner to other farmers in their social networks after the harvest. Logit model was used to analyze the factors associated with farmers’ decision to follow the structured diffusion of improved pulse varieties. Study revealed that majority of the farmers preferred 1:1 ratio for structured diffusion. The structured diffusion varied significantly, with respect to years and pulse crops. Variables like educational level, social participation, yield advantage accrued, attitude level and training exposure significantly determined the decision of farmer to follow the structured diffusion of quality seeds of pulse crops.